Musculoskeletal and perceptual responses of batsmen comparing high- and moderate-volume sprints between the wickets - Sheppard, Bronwyn Jane (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2012)
Background: Literature has associated repeated eccentric muscle actions with increased muscle damage of the muscles involved. Eccentric actions are typical in sports which are 'stop-start' in nature requiring rapid acceleration and deceleration, typical of a batting activity in cricket. Ultra-structural damage of the skeletal muscle as a consequence of repeated decelerating activities is associated with performance decrements, particularly muscle strength and sprinting speeds. This suggests that eccentric strength decrements may provide an indication for the development of muscle strain injuries during these activities. Despite these findings, limited research has identified the specific musculoskeletal demands placed on cricket batsmen, particularly with reference to various match intensities. Objective: The present study, therefore, sought to determine the specific musculoskeletal, physiological and perceptual demands placed on specialised batsmen during two work bouts of different intensities; one representing a highintensity work bout and the other a moderate-intensity work bout. The dependent variables of interest were muscle activation, isokinetic strength changes, heart rate, 'central' and 'local' ratings of perceived exertion (RPE), body discomfort and performance. Methods: The two experimental conditions, representative of a high- (HVR) and moderate-volume running (MVR) batting protocol, required players to perform a simulated batting work bout of either twelve or six runs an over, within a laboratory setting. Selected physiological, perceptual and performance measures were collected at specific time intervals throughout the work bout while the biophysical measures were collected prior to, and following both protocols. Results: Of the variables measured, heart rate, 'central' and 'local' RPE values were observed to increase significantly (p<0.05) over time. This increase was greater as a consequence of the HVR in comparison to the MVR. No change in sprint times was documented during the MVR, in contrast, significant (p<0.05) increases over time were observed during the HVR, further highlighting the elevated demands associated with this condition. In addition, an 'end spurt' was observed particularly following the HVR condition, suggesting athletes were conserving themselves through the adoption of a pacing strategy. Reductions in biceps femoris and semitendinosus muscle activation levels were observed following the HVR. This was further supported by the significantly greater levels of semitendinosus activation following the MVR when compared to the HVR. Peak concentric and eccentric knee extensor (EXT) (-17.17% and -16.07% respectively) and eccentric flexor (FLEX) (- 17.49%) values decreased significantly (p<0.05) following the HVR at 60Â°.s-1. In addition, concentric and eccentric total work produced by the flexors and eccentric extensors resulted in significantly (p<0.05) lower values due to the HVR. Conclusion: The intermittent high-volume batting work bout elicited elevated mean heart rates, perceived ratings of cardiovascular and muscular effort and sprint times. Furthermore, hamstring activation levels and muscle strength, particularly concentric strength of the dominant lower limb were negatively affected by the HVR condition. These results suggest elevated demands were placed on the hamstring musculature as a consequence of the HVR condition, indicating a greater degree of musculoskeletal strain and increased injury risk associated with running between the wickets at this intensity, representative of an aggressive batting scenario.
Keywords: Cricket -- Batting -- Physiological aspects; Cricket injuries; Musculoskeletal system -- Wounds and injuries